Corporate social disclosure: an analysis of the employee disclosure and their relation to the industrial law cases in Malaysia from year 2004 to 2008 / Rafizan Abdul Razak, Zaleha Mahat and Nor Aishah Mohd Ali - Abdul Razak, Rafizan; Mahat, Zaleha; Mohd. Ali, Nor Aishah Mohd All (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Most of the Corporate Social Disclosures (CSD) research conducted on the employees’ issue in Malaysia is confined to the nature, quality and quantity of disclosure in the companies’ annual reports; however, none has been noted to have been discussing the relationship between the employee disclosure and the Industrial Law cases in Malaysia. Thus, by using content analysis method, this study analyzed the annual reports of two sector listed in Bursa Malaysia (Industrial Product and Finance) for the purpose to identify the trend of the employee disclosure in companies annual report from the year 2004 to 2008, the extent of those disclosures as well as to establish whether there is any association between the employee disclosure and number of the Industrial Law cases in Malaysia related to the disclosures. The results of the analysis reveal that there is an increasing trend in terms of number of sentences disclosed on employee disclosure in the companies’ annual reports. In terms of extent of the disclosure, most companies have at least disclosed some form of information on employees with most companies disclosing between 1 to 50 numbers of sentences for all employees’ sub-themes. The study has also established that there is no significant relationship between the employee disclosure and the Industrial Law cases in Malaysia except for disclosures on ‘Duties on employee sub-theme which shows a significant positive relationship with number of Industrial Law cases reported which is related to this theme. Such situation may not be desirable for companies and this finding is inconsistent with what has been postulated in legitimacy theory where when such disclosures are made, companies always seek, to show their positive contribution to the society by legitimizing their activities in order to protect the corporation’s self-interest.